2019
DOI: 10.1111/jpg.12734
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the Timing and Depositional Conditions of the Maikop Formation Within the Kura Basin, Eastern Azerbaijan, Through the Application of Re‐os Geochronology and Chemostratigraphy

Abstract: The Oligocene -Miocene Maikop Formation is the key source rock in the South Caspian and Kura Basins. The Maikop is composed of a thick (up to 3 km) succession of clay-rich mudstones containing up to 15% total organic carbon (TOC). Despite decades of study, the mudstones often lack precise age control -Maikop strata rarely contain diagnostic microfaunal assemblages which can be used for dating, stratigraphic correlation, or constraining the depositional setting. Using rhenium-osmium geochronology, this study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…2). The large sampling interval was not considered to be a problem, as Washburn et al (2019) observed relatively similar Re-Os values over several metres of stratigraphy. The selected samples were polished with silica carbide grit pads to minimize weathering effects and to remove any contamination by metal tools.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…2). The large sampling interval was not considered to be a problem, as Washburn et al (2019) observed relatively similar Re-Os values over several metres of stratigraphy. The selected samples were polished with silica carbide grit pads to minimize weathering effects and to remove any contamination by metal tools.…”
Section: Methodsmentioning
confidence: 99%
“…The initial 187 Os/ 188 Os ratios of high TOC samples with (moderately) high HI values near the base of member A (0.70 ± 0.03) and near its top (0.80 ± 0.14 and 0.56 ± 0.13, Washburn et al, 2019) are either higher or lower than that of the contemporaneous global ocean (0.61 ± 0.05 and ~0.72; Peucker-Ehrenbrink and Ravizza, 2020). This indicates that there was limited connectivity between the Eastern Paratethys and the global ocean during deposition of these sediments, and suggests that basin restriction resulted in (slightly) higher organic matter preservation as reflected by the higher HI values.…”
Section: Maikop Group (Islamdag Section)mentioning
confidence: 98%
See 2 more Smart Citations
“…To the south of the Greater Caucasus within Azerbaijan, a thick Maikopian sequence with excellent sourcerock properties extends into the Kura Basin (e.g. Washburn et al, 2019). However, as the basin narrows into western Azerbaijan and eastern Georgia the proportion of coarse clastics increases, and although the Maikopian is present within the Adjara-Trialeti Basin in the Tbilisi region, and locally appears to exceed 3000 m in thickness, its source potential is poor.…”
Section: Palaeogeographic Mapsmentioning
confidence: 99%